TEACHERS’ DIFFICULTIES IN IMPLEMENTING THE 2013 CURRICULUM - Rian Juanda; Anjas Pratama; Wita Rela Ningsih; Nur Baiti; Siti Raudhah; Nina Afriani; Siti Barliana (Program Studi Pendidikan Bahasa Inggris, 2020)
The implementation of the 2013 Curriculum is the continuity of the implementation of the Competency-Based Curriculum and School-Based Curriculum, which includes integrated competency of attitudes, knowledge, and skills. It is not as easy as imagined since, in reality, it has been found some obstacles in implementing it. Therefore, the primary purpose of this research is to find out and describe the obstacles faced by teachers in implementing it. Moreover, the researchers used descriptive research design to achieve its goal. The research samples were English teachers who were from several different juniors and senior high schools. Then the researchers used a questionnaire and interview to gather the corpus. After analyzing the data, it found that they do not get significant obstacles in preparing the Lesson Plans. However, some points as evaluation are obstacles in adjusting the character values ​​based on the basic material competencies, and incompatibility between the materials in the syllabus and the 2013 Curriculum textbooks. Also, they find the difficulties in learning implementation such as how to bring applicative skills in the learning process, how to foster the students' creativity with the limited facilities, and how to apply the scientific approach stages especially for